The impact of a statement: more detail does not always help - Freedman, Jonathan L. (Legal and criminological psychology, 1996)
Three studies investigated the effect of the amount of detail in a statement on the impact of that statement on participants' judgements of someone's guilt. When the honesty of the person making the statement was not an issue, over a broad range, more details increased impact. However, when there was some possibility that the person was lying, maximum impact was produced by an intermediate level of detail. It is suggested that similar effects may occur with other factors that ordinarily increase acceptance of a statement.